Monetary policy communication: Evidence from Survey Data - Neda Popovska-Kamnar (National Bank of the Republic of Macedonia, 2017)
This paper summarizes the results of a Survey on Monetary policy Communication conducted among central banks in Central Eastern and South-Eastern Europe and the euro area. The main objective of this Survey was to draw evidence on the level of transparency and communication strategies of the central banks. The results of the Survey reveal that today the central banks pay much attention to the proper transparency and provide significant information about their decisions and policy making process. The overall conclusion of the Monetary policy communication Survey is that the communication and the transparency of the 15 central banks included in the Survey is on satisfactory level. Still, there is always a room for improvement, especially in the area of introducing forward guidance by the central banks and more "proactive ways" of communication with the public.
Keywords: E52; E58; E66; G01; 330; survey data; central banks; monetary policy; communication; transparency